RESPON VARIETAS JAGUNG (Zea mays var. saccharata Sturt) MANIS TERHADAP KOMPOS TITHONIA PADA SAWAH ULTISOL - Widodo Haryoko; Zahanis Zahanis; Vera Murdi; Aslan Sari Thesiwati; Milda Ernita; Afri Rona Diyanti; M. Zulman Harja Utama; Sunadi Sunadi; Yopa Dwi Mutia (Jurnal Sains Agro, 2023)
The objective of the experiment was to determine the response of sweet corn varieties to Thitonia compost in ultisol rice fields. The experiment was conducted in Kalumbuk Village, Kuranji District, Padang City from September – November 2021. The experiment was carried out using a completely randomized factorial design with the first factor being sweet corn varieties namely Bonanza, Asia 86, and Paragon, while the second factor was the dosage of Thitonia compost consisting of 4 levels namely 0 , 4, 8, and 12 tonnes ha-1. The combination of the two factors is repeated 3 times. Based on the experimental results, it was concluded that the response of the sweet corn varieties Bonanza, Asia 86 and Paragon showed a variety of growth, showed a variety of yield components and a variety of production in ultisols. Sequentially the highest production was obtained by the Asian variety 86 namely 18.00 t ha-1, followed by the Bonanza variety, namely 17.43 t ha-1 and Paragon variety, namely 16.44 t ha-1 with dosage Thitonia compost namely 8 t ha-1.